Catalysis of water oxidation in acetonitrile by iridium oxide nanoparticles. Issue 3 (27th October 2014) - Hidalgo-Acosta, Jonnathan C.; Méndez, Manuel A.; Scanlon, Micheál D.; Vrubel, Heron; Amstutz, Véronique; Adamiak, Wojciech; Opallo, Marcin; Girault, Hubert H.
Abstract : Micro-domains of water molecules surrounded by organic solvent exhibit enhanced reactivity towards oxidation compared to highly hydrogen-bonded bulk water molecules. Abstract : Water oxidation catalysed by iridium oxide nanoparticles (IrO2 NPs) in water–acetonitrile mixtures using [Ru III (bpy)3 ] 3+ as oxidant was studied as a function of the water content, the acidity of the reaction media and the catalyst concentration. It was observed that under acidic conditions (HClO4 ) and at high water contents (80% (v/v)) the reaction is slow, but its rate increases as the water content decreases, reaching a maximum at approximately equimolar proportions (≈25% H2 O (v/v)). The results can be rationalized based on the structure of water in water–acetonitrile mixtures. At high water fractions, water is present in highly hydrogen-bonded arrangements and is less reactive. As the water content decreases, water clustering gives rise to the formation of water-rich micro-domains, and the number of bonded water molecules decreases monotonically. The results presented herein indicate that non-bonded water present in the water micro-domains is considerably more reactive towards oxygen production. Finally, long term electrolysis of water–acetonitrile mixtures containing [Ru II (bpy)3 ] 2+ and IrO2 NPs in solution show that the amount of oxygen produced is constant with time demonstrating that the redox mediator is stable under these experimental conditions.